2020
DOI: 10.33963/kp.15606
|View full text |Cite
|
Sign up to set email alerts
|

Football spectatorship and selected acute cardiovascular events: lack of a population-scale association in Poland

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…In type I, researchers directly examined the association between the presence or severity of anxiety and subsequent SCA or SCD (n = 7 studies) (17)(18)(19)(20)(21)(22)(23). In type II, researchers compared the rates of SCA or SCD during or directly after a public event likely to be accompanied by mental stress (Covid-19 pandemic, earthquakes, terrorist attack, important football tournaments) with those during control periods (n = 8 studies) (24)(25)(26)(27)(28)(29)(30)(31). In type III, researchers retrospectively examined the life events in the period before SCA described by SCA survivors or relatives of SCA victims as compared with control persons or periods (n = 5 studies) (32)(33)(34)(35)(36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In type I, researchers directly examined the association between the presence or severity of anxiety and subsequent SCA or SCD (n = 7 studies) (17)(18)(19)(20)(21)(22)(23). In type II, researchers compared the rates of SCA or SCD during or directly after a public event likely to be accompanied by mental stress (Covid-19 pandemic, earthquakes, terrorist attack, important football tournaments) with those during control periods (n = 8 studies) (24)(25)(26)(27)(28)(29)(30)(31). In type III, researchers retrospectively examined the life events in the period before SCA described by SCA survivors or relatives of SCA victims as compared with control persons or periods (n = 5 studies) (32)(33)(34)(35)(36).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study found a significantly increased incidence of SCD in Swiss men and women during the FIFA World Cup 2002 as compared with the control period (30). Two other studies, covering four tournament periods, found no significant associations between football spectatorship and the incidence of SCA in Polish men (25) or German men and women in the province of Bavaria (27).…”
Section: Football Matchesmentioning
confidence: 98%
See 1 more Smart Citation